1996
DOI: 10.1021/bi960269o
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functional Positive and Negative Thyroid Hormone-Responsive Elements in the Rat Apolipoprotein AI Promoter

Abstract: Transcription of the antiatherogenic protein apolipoprotein AI is regulated by the thyroid hormone, L-triiodothyronine. Transient transfection and electrophoretic mobility shift assays were used to identify the cis-acting elements involved. In transient transfection assays, hormone bound to either thyroid hormone receptor alpha or beta exerts a positive effect through a thyroid hormone response element, site A (-208 to -193). In the absence of site A, liganded receptor alpha or beta have a negative effect on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 54 publications
3
44
0
Order By: Relevance
“…see [14]) binds to the given core promoter. In some cases, hormone receptors may in fact bind at either the immediately proximal side of the TATA box or over the initiator site, sterically blocking transcription complexes from binding to the promoter [15][16][17][18]. The regulation of transcription of either hormone-sensitive or other genes is considered to be to a large extent determined by its character as a TATA-box-dominated or initiator-dominated promoter, since most eukaryotic genes appear to be sufficed by the presence or action of only one of these two elements.…”
Section: Introductionmentioning
confidence: 99%
“…see [14]) binds to the given core promoter. In some cases, hormone receptors may in fact bind at either the immediately proximal side of the TATA box or over the initiator site, sterically blocking transcription complexes from binding to the promoter [15][16][17][18]. The regulation of transcription of either hormone-sensitive or other genes is considered to be to a large extent determined by its character as a TATA-box-dominated or initiator-dominated promoter, since most eukaryotic genes appear to be sufficed by the presence or action of only one of these two elements.…”
Section: Introductionmentioning
confidence: 99%
“…The complex TRE in the TSH gene contains a palindrome that activates and an independent half-site that mediates binding of a monomer of T3R and repression of transcription (11,12). Similarly the TRE in thyrotropin-releasing hormone and apolipoprotein A1 genes contains a complex element that involves the T3R monomer and a T3R-RXR heterodimer (13,14). Furthermore, formation of a monomer ϩ homodimer of GR was found to inhibit transcription of the POMC gene (15).…”
mentioning
confidence: 99%
“…Transcription of the apoA 1 gene is regulated by several hormones and second messengers, including retinoids (Zolfagari & Ross 1994), insulin (Murao et al 1998, Hargrove et al 1999, thyroid hormone (Mooradian et al 1996, Taylor et al 1996b, sex hormones (Patsch et al 1980, Harnish et al 1998, and others (Taylor et al 1996a, Vu-Dac et al 1998, Murao et al 1997. Several of these pathways function to increase the expression of the apoA 1 gene, whereas others act to decrease apoA 1 gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…This element is also responsible for induction of the apoA 1 gene by insulin (Murao et al 1998). Likewise, thyroid hormone can act as either a transcriptional enhancer or, in a more artificial fashion, as a transcriptional repressor (Taylor et al 1996b). The enhancer effect requires the presence of a thyroid hormone response element (TRE) located between nucleotides 208 and 193, in site A (Taylor et al 1996b), whereas the repressor effect is observed only when the TRE in site A is removed from reporter constructs, and requires the presence of a negative TRE (nTRE), AGGTCA, located between nucleotides 25 and 20.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation